Morphologic Characterization of Trigeminothalamic Terminal Arbors Arising From the Principal Nucleus in the Macaque - Andrew, Dona Lee E.; May, Paul J.; Warren, Susan (Frontiers in Neuroanatomy, 2020)
The ventral posterior medial nucleus (VPM) is a mandatory relay for orofacial sensory information targeting primary somatosensory cortex. We characterized the morphology of VPM axons arising in the principal trigeminal sensory nucleus (pV) through injections of biotinylated dextran amine placed in pV of Macaca fascicularis and mulatta monkeys. Labeled terminals formed a patchy bilateral distribution. Within contralateral VPM, patches were found primarily, but not exclusively, within the laterally located, vertical segment, and in ipsilateral VPM, primarily, but not exclusively, in the medially located, horizontal segment. Two fiber types were labeled: thin and thick. Thin fibers were poorly branched and diffusely distributed. They were studded with small en passant boutons. Most labeled fibers were thick and they branched extensively to form distinctive terminal arbors decorated with numerous boutons that varied in size and shape. Quantitative analysis of thick fiber arbor features showed little difference between the sides, although contralateral boutons were significantly larger than ipsilateral ones. Bouton distribution with respect to counterstained somata suggests that proximal dendrites are their main target. Indeed ultrastructural examination demonstrated that they provide large diameter dendrites with numerous contacts. Direct comparison of thick fiber terminal arbors to cytochrome oxidase (CO) staining revealed that these arbors are much smaller than individual CO-rich patches believed to designate rods containing discrete body area representations. Thus, each terminal arbor appears to heavily innervate a small number of VPM neurons within a rod. This relationship would serve to maintain relatively small receptive fields within the topographic representation of the face.